IDENTIFICATION OF STAPHYLOCOCCUS ISOLATES FROM PORCINE TONSILS BASED ON MORPHOLOGICAL CHARACTERISTICS AND COAGULASE TEST - Ramadhan, Muhammad Agie; Suardana, I Wayan; Suarsana, I Nyoman (Buletin Veteriner Udayana, 2025)
Pig (Sus scrofa domesticus) are valuable livestock animals in the farming industry, known for their high economic productivity as a meat source. However, pigs are susceptible to microbial infections, especially during early growth stages. One of the primary components of the pig's immune system is the tonsils, which serve as the first barrier against pathogenic microorganisms entering through the mouth and respiratory tract. In young pigs, the tonsils frequently become colonization sites for Staphylococcus sp., a group of Gram-positive, grape- like coccus-shaped bacteria found in various body tissues. S. aureus, a specific species of Staphylococcus, is known to be coagulase-positive with high pathogenic potential, while S. epidermidis, which is coagulase-negative, is generally considered a commensal species. The coagulase test is a critical laboratory method for distinguishing these species based on their ability to produce the coagulase enzyme, which clots blood plasma. This study aims to identify Staphylococcus isolates in the tonsils of young pigs and assess their pathogenic potential using the coagulase test. A total of 40 presumptive Staphylococcus sp. isolates were obtained and tested. The results showed that 14 isolates (35.8%) were coagulase-positive and identified as S. aureus, which poses a potential risk of serious infections in animals. Meanwhile, 26 isolates (64.2%) were coagulase-negative and identified as S. epidermidis, which is typically non- pathogenic. This study highlights the importance of the coagulase test in identifying Staphylococcus species and assessing infection risks, which is beneficial for improving pig health and productivity in farming environments.